STRATEGI PENGEMBANGAN KARAKTER SISWA MELALUI EKSTRAKURIKULER DI MTs AZZAINABIYAH SRESEH SAMPANG - Syarifah yasum; Linda Ramadhanty Januar; Sahrul Muzekki (Jurnal Cendekia Pendidikan, 2025)
The crisis of character and morality among students has become a crucial issue in modern education. This phenomenon has sparked controversy because character development in schools is often not managed systematically in terms of planning and implementation. The paradigm shift in education requires new strategies that place extracurricular activities as an effective medium for shaping students' character values. This study aims to analyze: (1) teachers' strategies in developing student character through extracurricular activities at MTs Azzainabiyah Sreseh Sampang, and (2) the supporting and inhibiting factors in the development process. The study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results show that character development strategies are carried out through three main approaches: understanding and practicing value concepts, providing role models by teachers, and creating a character-building atmosphere in every extracurricular activity. The dominant character values that develop include nationalism, cooperation, independence, discipline, and creativity. Supporting factors include collaboration between the principal, guidance counselors, student enthusiasm, and parental support, while the main obstacles lie in time constraints, lack of student motivation, and environmental influences. These findings confirm that extracurricular activities can be a strategic solution in building students' character holistically.